Synergy among knowledge systems for sustainable agriculture: Lessons for G20 nations from India - Singh, Ranjay K; Singh, Dheeraj; Maiti, Sanjit (Indian Farming, 2023)
Agricultural sustainability is essential for addressing climate change, arresting biodiversity loss and ensuring food security. However, a balanced relationship between cultural ideals, environmental conditions and economy is crucial for using, and creating new information through a synergy among the knowledge systems. Agricultural communities world over have evolved local knowledge systems that help in conserving natural resources, while scientific knowledge, developed by agricultural research institutions, play vital role in either eliminating agricultural issues directly or through strengthening local knowledge systems. Additionally, agricultural extension services gather and integrate such knowledge systems by constantly interacting with farmers and other stakeholders. These diverse knowledge system and related practices may aid context-specific management of agricultural resources and strengthening resilience strategies. Such resources are valuable in developing agricultural technologies, capacity building and coherent policies for G20 nations. With sharing and collaboration on knowledge systems, policy coordination, financial support to developing nations and partnerships, G20 nations can facilitate debates on knowledge management system and ensuring the sustainable agriculture.